Contribution of Non-Formal Education to Improve the Quality of Human Resources - Melania Melania; Abdul Kadir; Anton Respati Pamungkas; Sachin Gupta (Universitas Negeri Semarang, 2024)
Education is a pillar of a country's development and economy. Non-formal education is organized to serve people who need access to education to improve their quality of life. Non-formal education focuses on training and developing skills to develop and improve the quality of human resources in order to be able to solve problems that occur and compete globally in the labor market. Improvement and development of the quality of human resources can be done through non-formal education platforms. This study aims to identify efforts to improve the quality of human resources, especially productive age through the contribution of non-formal education to produce quality human resources to be able to compete both on a local and international scale. This research is designed by adopting a qualitative research approach and includes the type of literature study research. Data were collected through literature study methods obtained from scopus indexed journals that focus on the effectiveness of non-formal education and the contribution of non-formal education to improving the quality of human resources. The results showed that in essence human resource development is very important so that the potential possessed by each community can be optimized and one of them can be realized through education. Soft skills such as communication and leadership must be possessed by every human resource in order to be able to overcome uncertainty and survive in the world of work. These soft skills can be obtained through non-formal education programs. Improving the quality of human resources through non-formal education must also be followed by improving the quality, efficiency, and effectiveness of continuing education. In addition, improving the quality of human resources through non-formal education programs must also be followed by increasing education funding so that it can run optimally.